Policy instruments for political capacity: lessons from three infrastructure projects in the Brazilian Amazon (Gestão & Regionalidade, 2024)
The ongoing debate over development strategies highlights the importance of infrastructure to boost economic and social growth, but several studies have pointed to state capacity deficits to plan and implement infrastructure projects. This paper aim to investigate the construction of policy instruments for political state capacity to implement large hydroelectric plants in the Brazilian Amazon, based on the congruence method to produce evidence of three hydroelectric plants. Data analysis reveals that despite the development and activation os policy instruments in the Brazilian democratic era, these were not enough to produce high levels of political capacity, then state bureaucracies still fail in addressing the demands of vulnerable groups. This can be explained by asymmetrical development of political capacity in the structure of public administration; the use of political capacity instruments in the advanced stages of the policy process; the contestation of the mapped demands from participatory process by state bureaucracies.
Keywords: Amazon; Brazil; Hydroelectric Plants